Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1136/ard.2009.111187
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of the Ankylosing Spondylitis Disease Activity Score (ASDAS) and clinical and MRI measures of disease activity in a 1-year follow-up study of patients with axial spondyloarthritis treated with tumour necrosis factor α inhibitors

Abstract: ASDAS demonstrates construct validity and high responsiveness during treatment with TNFalpha inhibitors in patients with SpA. The proposed thresholds for disease activity and treatment response need further validation. Trial registration number NCT00133315.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 26 publications
4
65
2
3
Order By: Relevance
“…Moreover, it was stated that ASDAS showed better correlation and higher discriminative ability than BASDAI in patients with AS [11]. Several studies showed that ASDAS is reliable and reproducible and in some cases better than BASDAI [12,13]. Although it is difficult to calculate without using a calculator [9,11], the availability of desktop and smartphone calculators for ASDAS has lessen this problem considerably.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, it was stated that ASDAS showed better correlation and higher discriminative ability than BASDAI in patients with AS [11]. Several studies showed that ASDAS is reliable and reproducible and in some cases better than BASDAI [12,13]. Although it is difficult to calculate without using a calculator [9,11], the availability of desktop and smartphone calculators for ASDAS has lessen this problem considerably.…”
Section: Introductionmentioning
confidence: 95%
“…In the initial studies of adult patients with IBP of less than 2 years, these diagnostic and classificatory properties of both the ASAS axial and peripheral SpA criteria appear to be better than those of reported by Amor, et al [37] and ESSG [38] groups and implementation is under way. Drug efficacy studies are being carried out in patients with axial SpA to determine the role of TNF blockers in remission and prevention of structural damage [71-73]. …”
Section: Reviewmentioning
confidence: 99%
“…Therefore, it would be beneficial to identify biomarkers of inflammation that accurately reflect the findings of MRI in axSpA patients. CRP levels show a moderate correlation with MRI inflammation scores [33], but the results are inconsistent [35,36]. Recent studies identified new biomarkers of inflammation, including markers of angiogenesis and tissue turnover.…”
Section: Discussionmentioning
confidence: 99%